The Influence of Transformational Leadership, Work Competency, and Work Discipline on Work Productivity with Job Satisfaction as a Mediating Variable on Employees of the Aceh Human Resources Development Agency - Sari, Rahma; Sulaiman,; Halimatussakdiah, (International Journal of Scientific Research and Management (IJSRM), 2024)
This study investigates the correlation between transformational leadership, work competency, discipline, and work productivity at the Aceh Human Resources Development Agency (BPSDM Aceh) with job satisfaction as a moderating variable. Questionnaires were sent to 99 BPSDM Aceh workers as the main means of data collection in this research. The data analysis of this research made use of the Structural Equation Model Partial Least Square (SEM PLS). The SmartPLS software paradigm is employed to facilitate data processing for research objectives. The result shows that directly, transformational leadership and work competency do not significantly affect job satisfaction, while work discipline significantly affects job satisfaction; transformational leadership, work competency, and work discipline significantly affect work productivity, and; indirectly, transformational leadership and work competency does not significantly affect work productivity through mediation of job satisfaction, while work discipline significantly affects work productivity through mediation of job satisfaction. The results also show that job satisfaction functions as a partial mediation on the impact of work discipline on work productivity.